KINERJA DAN PERSPEKTIF PENGEMBANGAN MODEL AGROPOLITAN DALAM MENDUKUNG PENGEMBANGAN EKONOMI WILAYAH BERBASIS AGRIBISNIS - RUSASTRA, I WAYAN; -, HENDIARTO; M. NOEKMAN, KHAIRINA; SUPRIATNA, ADE; K. SEJATI, WAHYUNING; HIDAYAT, DERI (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 2 Juli 2005, 2012)
The implementation of agropolytant have strong justification and considered to be a breakthrough program to strengthen the achievement of agribusiness development for the benefit of the farmers as well as regional economic development. The study consists of two main activities, i.e.: (a) To evaluate the concept and the achievement of agropolytant program; and (b) To assess the ongoing agropolytant pilot project. The strengthening of agropolytant development has to be facilitated with suitable strategic policies of domestic price stability, better accessibility to input market and processing, better urban functionality, and accelerated rural-urban flow for the benefit of rural people. In addition, the policy of agropolytant program credit scheme (BLM) have to be complemented and facilitated with strong self-help farmer group and cooperative marketing institutional development. Agropolytant development has been able to improve farmer income, but absolutely the farmer income is still low, due to restricted resource endowment. Agropolytant program working group (Pokja) at regency level has well functionality, and Agropolytant Regional Management Agency (BPKAP) at provincial and regency level are badly needed. The existence of BPKAP will have important role in supporting the efectivity, performance, and accountability of agropolytant program. Government support have been implemented well. The achievement of those facilities have to be complemented with proper incentive system for all parties participated in agropolytant development program.
Keywords: Agropolytant, Regional Economic Development, Rural-Urban Linkage.